Adult learning and social inequalities – Processes of equalisation or cumulative disadvantage? - Elina Kilpi-Jakonen; Daniela Vono de Vilhena; Hans-Peter Blossfeld (Springer Netherlands, 2025)
Adult learning is an increasingly important form of education in globalised and aging societies. While current policy recommendations tend to focus on increasing participation rates, the authos of this article argue that higher participation rates do not necessarily lead to lower social/educational inequalities in participation. The aim of this paper is to examine the relationship between social inequalities and adult learning by exploring cross-national patterns of participation in different adult
learning activities and the consequences of participation on individual labour market trajectories. The empirical basis of the paper is an analysis of 13 country studies (as well as two cross-national analyses) brought together by the international comparative research project ‘‘Education as a lifelong process – comparing educational trajectories in modern societies’’ (eduLIFE). Despite wide variations in participation rates across countries, mechanisms of social/educational inequality in engagement in
job-related adult learning tend to be relatively similar across countries, in particular with regard to non-formal learning. Effects tend most frequently to be a presence of cumulative advantage, though in some countries a certain degree of equalisation is noticeable with regard to formal adult education. The authors conclude that it is relatively clear that currently almost no country is truly able to reduce social inequalities through adult learning. Their recommendation is that public policy makers should place greater emphasis on making adult learning more accessible (in terms of entry requirements, affordability as well as motivation) to underrepresented groups, in particular those who are educationally disadvantaged.